SKI-1/S1P Facilitates SARS-CoV-2 Spike Induced Cell-to-Cell Fusion via Activation of SREBP-2 and Metalloproteases, Whereas PCSK9 Enhances the Degradation of ACE2 - Rachid Essalmani; Ursula Andréo; Alexandra Evagelidis; Maïlys Le Dévéhat; Oscar Henrique Pereira Ramos; Carole Fruchart Gaillard; Delia Susan-Resiga; Éric A. Cohen; Nabil G. Seidah (Viruses, 2023)
Proprotein convertases activate various envelope glycoproteins and participate in cellular entry of many viruses. We recently showed that the convertase furin is critical for the infectivity of SARS-CoV-2, which requires cleavage of its spike protein (S) at two sites: S1/S2 and S2′. This study investigates the implication of the two cholesterol-regulating convertases SKI-1 and PCSK9 in SARS-CoV-2 entry. The assays used were cell-to-cell fusion in HeLa cells and pseudoparticle entry into Calu-3 cells. SKI-1 increased cell-to-cell fusion by enhancing the activation of SREBP-2, whereas PCSK9 reduced cell-to-cell fusion by promoting the cellular degradation of ACE2. SKI-1 activity led to enhanced S2′ formation, which was attributed to increased metalloprotease activity as a response to enhanced cholesterol levels via activated SREBP-2. However, high metalloprotease activity resulted in the shedding of S2′ into a new C-terminal fragment (S2″), leading to reduced cell-to-cell fusion. Indeed, S-mutants that increase S2″ formation abolished S2′ and cell-to-cell fusion, as well as pseudoparticle entry, indicating that the formation of S2″ prevents SARS-CoV-2 cell-to-cell fusion and entry. We next demonstrated that PCSK9 enhanced the cellular degradation of ACE2, thereby reducing cell-to-cell fusion. However, different from the LDLR, a canonical target of PCSK9, the C-terminal CHRD domain of PCSK9 is dispensable for the PCSK9-induced degradation of ACE2. Molecular modeling suggested the binding of ACE2 to the Pro/Catalytic domains of mature PCSK9. Thus, both cholesterol-regulating convertases SKI-1 and PCSK9 can modulate SARS-CoV-2 entry via two independent mechanisms.